O efeito da concentração inicial de demanda química de oxigênio (DQO), teor de biomassa e aeração na remoção de DQO, nitrogênio e fósforo de efluentes de indústria de vegetais congelados por reator em batelada sequencial (RBS) - Betto, Thaís Luciana (2009)
The wastewater generated by food industries contains high COD levels, besides large amounts of nutrients, causing a negative impact when released into the water without proper treatment. The use of alternative technologies, such as Sequential Batch Reactor (SBR) for the wastewater treatment has been studied around the world. The objective of this work was to study the biological treatment of frozen vegetables industry wastewater in a SBR, verifying its performance on the biological removal of carbon and nutrients (nitrogen and phosphorus) in order to obtain a treated wastewater that attends the discharging standards recommended by the Brazilian environmental legislation. In this study, the treatment of frozen vegetables industry wastewater was done in a SBR laboratorial scale, using biomass level ranging from 2000 mg.L-1 to 4000 mg.L-1, CODi ranging from 300 mg.L-1 to 600 mg.L-1 and air flow (aeration) ranging from 3 L.min-1 to 6 L.min-1. The results show that the removal efficiency for COD has been achieved in the experiment 3, with removal levels of 88%. For TAN, the best removal levels has been achieved in the experiment 14 with removal levels of 74,9 %. The optimized conditions to the COD and TAN removal of frozen vegetables industry wastewater is: Initial COD of 600 mg.L-1, aeration of 4,5 L.min-1 and biomass level of 2000 mg.L-1. The SBR showed to be easy to in the operation and control, being an important alternative for agroindustry wastewater carbon and nutrients removal